2022
DOI: 10.1371/journal.pone.0279689
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for in silico assessment of Methionine oxidation risk in monoclonal antibodies: Improvement over the 2-shell model

Abstract: Over the past decade, therapeutic monoclonal antibodies (mAbs) have established their role as valuable agents in the treatment of various diseases ranging from cancers to infectious, cardiovascular and autoimmune diseases. Reactive groups of the amino acids within these proteins make them susceptible to many kinds of chemical modifications during manufacturing, storage and in vivo circulation. Among these reactions, the oxidation of methionine residues to their sulfoxide form is a commonly observed chemical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…It has been reported in different studies that the amino acids such as methionine, histidine, tryptophan, tyrosine, and phenylalanine were found in the oxidized state due to the presence of various reagents. ,, For example, in a previously published report by Glover et al, the oxidation in the same mAb (mAb1) used in this study, but produced by a different manufacturer, was analyzed upon exposure to Fe 2+ and H 2 O 2 in formulation buffer , and it was found that methionine at 255 and 431 positions in the heavy chain of the mAb was oxidized. Furthermore, various studies have reported different metal and various oxidative agent mediated degradation of proteins including mAb. ,, In this work, fragments were also observed in the SEC chromatogram of mAb samples in saline containing both Fe 2+ and H 2 O 2 . The fragments in SEC chromatogram obtained beyond 37 min and the ones that possibly interacted with metal/H 2 O 2 were not characterized.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has been reported in different studies that the amino acids such as methionine, histidine, tryptophan, tyrosine, and phenylalanine were found in the oxidized state due to the presence of various reagents. ,, For example, in a previously published report by Glover et al, the oxidation in the same mAb (mAb1) used in this study, but produced by a different manufacturer, was analyzed upon exposure to Fe 2+ and H 2 O 2 in formulation buffer , and it was found that methionine at 255 and 431 positions in the heavy chain of the mAb was oxidized. Furthermore, various studies have reported different metal and various oxidative agent mediated degradation of proteins including mAb. ,, In this work, fragments were also observed in the SEC chromatogram of mAb samples in saline containing both Fe 2+ and H 2 O 2 . The fragments in SEC chromatogram obtained beyond 37 min and the ones that possibly interacted with metal/H 2 O 2 were not characterized.…”
Section: Discussionsupporting
confidence: 51%
“…The generation of excessive ROS due to the reaction between metal ions and H 2 O 2 is responsible for the rapid degradation of proteins. Fenton reaction, which leads to the formation of hydroxyl free radicals, has been studied in many chemical and biochemical systems. ,, The free radicals perturb the protein structure by oxidatively damaging the amino acids, eventually leading to the formation of aggregates and breakage of polypeptide chains. ,, There are various published studies where the oxidation of amino acids and oxidation mediated damage of proteins in terms of aggregation and fragmentation have been explored. ,, The detailed mechanism of Fenton-reaction-mediated aggregation is shown in Figure . Furthermore, interactions of metal ions to the protein backbone and amino acids, and the presence of nonprotein components in protein aggregates have also been published in various studies which explored metal-catalyzed degradation of proteins. ,, Hence, non-protein components in aggregates of mAb in the current study can be characterized further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of human pancreatic alpha-amylase in complex with myricetin (MYC) was obtained from the Protein Data Bank (PDB ID: 4GQR) [ 50 ]. The protein was prepared for further analysis using the Protein Preparation Wizard in Maestro Schrödinger [ 51 ]. This included the addition of missing hydrogen atoms to the residues, the correction of metal ionization states, and the removal of water molecules beyond 5 Å.…”
Section: Methodsmentioning
confidence: 99%
“…The sequence data for PRX002 was obtained from the Kyoto Encyclopedia of Genes and Genomes (KEGG) [31], and Schrödinger software BioLuminate [32, 33, 34, 35, 36, 37] and PyMol [38] were used to predict the protein structure of the Fab region of the mAb, with Chothia numbering used to annotate the final models. Thirty-four different variations of α-syn were obtained from the Protein Data Bank (PDB ID 2KKW [34]), which all had different structures gathered by nuclear magnetic resonance imaging.…”
Section: Methodsmentioning
confidence: 99%